THE DIFFERENCE IN CONSUMER RISK PERCEPTION BETWEEN CELEBRITY ENDORSER AND EXPERT ENDORSER IN COLLEGE ADVERTISEMENTS - Soliha, Euis; Zulfa, Naila (Journal of Indonesian Economy and Business, 2009)
This research aims to examine the difference in consumer risk perception betweenÂ celebrity and expert endorser in advertisement. We proposed two hypothesis, H1: There isÂ a difference in consumer risk perception between an expert endorser and celebrityendorser in college advertisement. H2: There is a difference in consumer risk perceptionÂ between an expert endorser and a celebrity endorser in college advertisement, which isÂ moderated by the consumer product knowledge.Experimental design was employed in this study with Statistical Experimental-Completely Randomized Design. This was conducted on three groups to test H1 and sixÂ groups to test H2. To test H1, the participant of each group was given full color print adsÂ using celebrity endorser, expert endorser and nonendorser in advertisement. We gofurther splitting each group with high and low consumer product knowledge to test H2.The participants of this research are 200 students of SMA 7 Semarang.Â We use One Way Anova to test H1 and two ways Anova to test H2. Our findingsÂ showed that there is a difference in consumer risk perception between an expert endorserÂ and celebrity endorser in college advertisement. We also found that there is no differencein consumer risk perception between an expert endorser and a celebrity endorser inÂ collegeâs advertisement, which is moderated by the consumer product knowledge. We alsoÂ found that there is difference in consumerâs perceived performance risk, consumerâsperceived financial risk and consumerâs social risk between an expert and celebrityÂ endorser in College advertisement. On the other hand, we found there is no difference inÂ consumer perceived psychological risk between an expert and celebrity endorser inÂ College advertisement.Keywords: celebrity endorser, expert endorser, consumer risk perception, consumerÂ product knowledge.